Transcriptional regulation of the calcitonin receptor gene. (August 2002) - Pondel, M. D.; Jagger, C.; Hebden, C.; Partington, G.; Mould, R.
Abstract : Calcitonin is a 32-amino-acid peptide hormone that is produced by parafollicular cells of the thyroid gland in response to increased levels of extracellular calcium. In this article we review our previous and current research on the transcriptional regulation of the pig and human calcitonin receptor (CTR) gene. Initially, our experiments on the transcriptional analysis of the pig CTR gene in transgenic mice are examined, followed by our studies on the cloning of the human CTR (hCTR) gene promoter and its transcriptional activity in hCTR-positive cell lines. We further describe the activity of the hCTR promoter in transgenic mice and review current experiments to identify transcriptional regulatory elements and the transcription factors they interact with, which direct the tissue-specific expression pattern of hCTR promoter activity.